Effects of High-Frequency Chest Wall Oscillation on Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Huang HP; Chen KH; Tsai CL; Chang WP; Chiu SYH; Lin SR; Lin YH (International Journal of COPD, 2022)
Hsiao-Ping Huang,1 Kee-Hsin Chen,2– 6 Chen-Liang Tsai,7 Wen-Pei Chang,8,9 Sherry Yueh-Hsia Chiu,10,11 Shin-Rou Lin,10,11 Yu-Huei Lin2 1Nursing Department, Center for Nursing and Healthcare Research in Clinical Practice Application, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 2Post-Baccalaureate Program in Nursing, College of Nursing, Taipei Medical University, Taipei, Taiwan; 3Cochrane Taiwan, Taipei Medical University, Taipei, Taiwan; 4Department of Nursing, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 5Center for Nursing and Healthcare Research in Clinical Practice Application, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 6Evidence-Based Knowledge Translation Center, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 7Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 8Department of Nursing, Shuang Ho Hospital, Taipei Medical University, New Taipei City, Taiwan; 9School of Nursing, College of Nursing, Taipei Medical University, Taipei, Taiwan; 10Department of Health Care Management, College of Management, Healthy Aging Research Center, Chang Gung University, Taoyuan, Taiwan; 11Division of Hepatogastroenterology, Department of Internal Medicine, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, TaiwanCorrespondence: Yu-Huei Lin, Tel +886 2 27361661 Ext 3620, Fax +886 2 23772842, Email gracelin@tmu.edu.twPurpose: This study aimed to evaluate the efficacy of high-frequency chest wall oscillation for sputum expectoration and hospital length of stay in patients with acute exacerbations of chronic obstructive pulmonary disease. The improvements in pulmonary function and oxygenation were also investigated.Patients and Methods: This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidelines. Automated literature database searches were conducted from the earliest records to March 31, 2022. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool (RoB 2.0), and meta-analysis software (RevMan 5.4) was used to analyze the data.Results: From 5439 identified articles, 13 studies (with 756 patients) were included in this meta-analysis. Compared to other airway clearance techniques, HFCWO significantly increased expectorated sputum volume by 6.18 mL (95% CI: 1.71 to 10.64; I2 = 87%), shortened hospital stay by 4.37 days (95% CI: − 7.70 to − 1.05; I2 = 84%). However, FEV1 (%), PaO2, and PaCO2 did not improve significantly.Conclusion: AECOPD patients may benefit from HFCWO therapy. HFCWO enables AECOPD patients to excrete more sputum and shorten their hospital stays. However, due to heterogeneity among the included research, these results should be interpreted with caution.Keywords: acute exacerbation of chronic obstructive pulmonary disease, AECOPD, high-frequency chest wall oscillation, HFCWO, sputum expectoration, length of hospital stay